NUTRITIONAL PROBLEMS AMONG SCHOOLCHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The purpose of the review is to analyze and summarize the data available in the literature on the actual nutrition of schoolchildren in different subjects of Uzbekistan and abroad. In many regions of the country, there is insufficient consumption of the most biologically valuable foodstuffs: meat and meat products, milk and dairy products, fish and fish products. In many regions of the country, there is insufficient consumption of the most biologically valuable foodstuffs: meat and meat products, milk and dairy products, fish, eggs, vegetable oil, potatoes, fruits and vegetables, with excessive consumption of bread, pasta and pasta. The nature of nutritional disorders in the population is often regionally specific. The main provisions of the review are the reasons leading to nutritional disorders of children in educational institutions. Numerous studies have found that many children have already formed irrational stereotypes of food choices by the time they start school.